Do mobile clinics provide high-quality antenatal care? A comparison of care delivery, knowledge outcomes and perception of quality of care between fixed and mobile clinics in central Haiti - Erica Phillips; Rebecca J. Stoltzfus; Lesly Michaud; Gracia Lionel Fils Pierre; Francoise Vermeylen; David Pelletier (BMC, 2017)
Abstract Background Antenatal care (ANC) is an important health service for women in developing countries, with numerous proven benefits. Global coverage of ANC has steadily increased over the past 30 years, in part due to increased community-based outreach. However, commensurate improvements in health outcomes such as reductions in the prevalence of maternal anemia and infants born small-for-gestational age have not been achieved, even with increased coverage, indicating that quality of care may be inadequate. Mobile clinics are one community-based strategy used to further improve coverage of ANC, but their quality of care delivery has rarely been evaluated. Methods To determine the quality of care of ANC in central Haiti, we compared adherence to national guidelines between fixed and mobile clinics by performing direct observations of antenatal care consultations and exit interviews with recipients of care using a multi-stage random sampling procedure. Outcome variables were eight components of care, and women's knowledge and perception of care quality. Results There were significant differences in the predicted proportion or probability of recommended services for four of eight care components, including intake, laboratory examinations, infection control, and supplies, iron folic acid supplements and Tetanus Toxoid vaccine provided to women. These care components were more likely performed in fixed clinics, except for distribution of supplies, iron-folic acid supplements, and Tetanus Toxoid vaccine, more likely provided in mobile clinics. There were no differences between clinic type for the proportion of total physical exam procedures performed, health and communication messages delivered, provider communication or documentation. Women's knowledge about educational topics was poor, but women perceived extremely high quality of care in both clinic models. Conclusions Although adherence to guidelines differed by clinic type for half of the care components, both clinics had a low percentage of overall services delivered. Efforts to improve provider performance and quality are therefore needed in both models. Mobile clinics must deliver high-quality ANC to improve health and nutrition outcomes.